ANALISIS PENGARUH ORIENTASI KEWIRAUSAHAAN, KOMPETENSI SDM, INOVASI, DAN KAPABILITAS SUMBER DAYA SUPPLIER TERHADAP KEUNGGULAN BERSAING INDUSTRI LOGAM MESIN DAN ELEKTRONIK DI KABUPATEN TEGAL - Ramdani, Dwi Kusuma; Rahardjo, Susilo Toto (Faculty of Economics and Business Diponegoro University, 2017)
Tegal Regency’s Metal Industry is one of the oldest metal industries in Indonesia. This industry began in Dutch colonial era, to meet the demand for equipment & spare part for sugar factory, rail way, shipping and textile factories. Metal Industries in Tegal Regency continues to grow until now, but few years back this industries experience decline, this is due to the difficulty to obtain raw materials and a lot of abroad products that enter Indonesia. This study aims to determine the relationship between entrepreneur orientation, human resource competencies, innovation and supplier resource capabilities to competitive advantage of metal industries in Tegal Regency.Using questionnaire to metal Industry owner in Tegal Regency and regression analysis, these four variables (entrepreneur orientation, human resource competencies, innovation and supplier resource capabilities) were tested whether they had an influence on competitive advantage, and how much influence they had.The results showed that the variables of entrepreneur orientation, human resource competency, innovation, and supplier resource capability affect the competitive advantage of metal industry in Tegal Regency either partially or simultaneously. However, only three have significant affect, namely supplier resource capability, human resource competence and innovation.